THE CORRELATION OF HEALTH SEEKING BEHAVIOR AND TRANSPORTATION MODE WITH PREHOSPITAL DELAY TIME IN PATIENTS WITH ACUTE CORONARY SYNDROME AT EMERGENCY DEPARTMENT OF REGIONAL PUBLIC HOSPITAL OF dr. T.C. HILLERS - Ode Irman; Sri Poeranto; Tony Suharsono (Faculty of Nursing, Universitas Jember, 2017)
Emergency conditions of the acute coronary syndrome (ACS) requires rapid and precise management. Prehospital delay time can result in deaths attributed to health seeking behavior and transportation mode. This research aimed to analyze the correlation of health seeking behavior and transportation mode with prehospital delay time in patients with Acute Coronary Syndrome at Emergency Department of Regional Public Hospital of dr. T.C. Hillers. The research design was observational analytic with cross sectional approach. The sample was 42 respondents obtained by using consecutive sampling. Data were collected with an interview in April-June 2017, then analyzed with univariate analysis and bivariate (Fisher test). The results showed that the majority of health seeking behavior of ACS patients was delayed to hospital (76.2%) and the mode of transportation used was public transportation (31%). Prehospital delay time most of which arrived late (> 120 min) (61.9%). Result of fisher test show there is correlation of health seeking behavior and transportation mode with prehospital delay time in patients with Acute Coronary Syndrome at Emergency Department of Regional Public Hospital of dr. T.C. Hillers. The results indicate the importance of improving patient referral systems, provide health counseling, provide village ambulances, support and organize Emergency Medical Services.